OPEN PROPORTIONAL ELECTION SYSTEM ACCORDING TO THE PERSPECTIVE OF CONSTITUTIONAL LAW - Rustam HS Akili (Sean Institute, 2022)
This study aims to analyze an open proportional electoral system from the perspective of constitutional law. This research was conducted by examining what is meant by a closed proportional electoral system, legal aspects related to an open proportional electoral system, and what are the advantages and disadvantages of this system. The research method used is a normative juridical approach by collecting data and information through literature studies related to constitutional law and an open proportional electoral system. The results of the study show that an open proportional electoral system reflects true democracy according to Law number 7 of 2017 because the people can actually elect their leaders and representatives in parliament directly. An open proportional system has advantages in encouraging greater political participation and representing more community groups and creating political stability. However, this system also has weaknesses in the government's ability to make effective and quick decisions due to minority votes in parliament, lack of representation of political parties due to the prominence of individual candidates and the complexity of voting. Therefore, this research provides several policy suggestions, such as increasing political education for the public, strengthening political parties as institutions that are able to represent the community well, and increasing social control and oversight mechanisms over the implementation of an open proportional electoral system.